INITIAL TRAINING: TEKNIK PEMELIHARAAN KENDARAAN PKP-PK SEBAGAI SARANA PEMENUHAN KOMPETENSI PERSONIL PKP-PK BANDAR UDARA DALAM KESIAPSIAGAAN KENDARAAN OPERASIONAL PKP-PK - Anton Abdullah; Wildan Nugraha; Sutiyo Sutiyo; Reyvaldo Fajriansyah Setiawan; Muhammad Iqbal Dwi Saputra; Ridho Priyama Putra (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
The purpose of the activity is that the trainees are capable to conduct airport rescue and fire fighter (ARFF)  vehicle maintenance properly based on any related regulations and manuals The methods used are competency-based training, classroom session for theoretical learning process, and practical session with trainers and simulators for the fulfillment of ARFF personnel knowledge, skills, and attitudes. ARFF Vehicle Maintenance Technique Initial Training went well and smoothly, with an average evaluation score of 80,614 (qualification: good), indicated that the learning objectives have been achieved.